STRENGTHENING ADOLESCENT SELF-REGULATION THROUGH SCHOOL-BASED PSYCHOLOGICAL EMPOWERMENT PROGRAMS - Rokhmah, Masfuukhatur (Bhakti: Jurnal Pengabdian Masyarakat, 2026)
Adolescence is a critical developmental stage characterized by increasing academic demands, emotional fluctuations, and the need for effective self-management skills. Many senior high school students experience difficulties in regulating time, emotions, and priorities, which may hinder both academic adaptation and psychological well-being. This study reports a school-based psychological empowerment program designed to strengthen self-regulation among students of a public senior high school in Indonesia. Using a pretest–posttest design, the program involved 323 tenth-grade students who participated in a structured intervention consisting of psychoeducation, self-reflection, case-based discussions, journaling exercises, and self-care training. Self-regulation was measured using the Short Self-Regulation Questionnaire (SSRQ). Quantitative analysis using paired-samples t-tests revealed a significant increase in self-regulation scores following the intervention (t(322) = −11.36, p < .001), indicating meaningful improvement in students’ ability to manage thoughts, emotions, and behaviors. Beyond statistical findings, qualitative observations suggested enhanced emotional awareness and reflective capacity among participants. This study contributes to the discourse on community engagement by demonstrating how school-based psychological empowerment can serve as a preventive and promotive strategy for adolescent development. Integrating self-regulation interventions within educational communities may support both academic readiness and long-term psychological well-being.